Effect of Leadership Style, Compensation on Commitment and its Implementation on Employee Performance (Case Study of Mitra Sejahtera Cooperative Employees PT Denso Group Indonesia) - Aji, Purnomo; Hidayat, Rahmat (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This observation intends to be able to determine the effect of leadership style, compensation on commitment and its implementation on the performance of Employees of the Mitra Sejahtera Cooperative PT. Denso Group. The total population in this study was 128 people with the determination of the number of samples using the slovin formula which produced 115 respondents. This study uses the Structural Equation Modeling (SEM) analysis model to be able to find out how much influence the independent has on the dependent variable through the intervening variable, carried out using the Lisrel 8.8 program. This research test succeeded in concluding that Leadership Style has a substantial effect on Commitment. Compensation has no substantial effect on Commitment. Leadership style has no significant effect on performance. Compensation turned out to have a positive and significant effect on performance. Commitment has a positive and substantial effect on performance. Leadership Style, Compensation has a substantial effect on Commitment. Meanwhile, Leadership Style, Compensation, Commitment have a substantial effect on performance. Then the Commitment variable becomes a mediator between the Leadership Style and Performance variables. And the Commitment variable becomes a mediator between the Compensation variable on performance.